Social Responsibility, the Concept and the Cognitive Background - Mokhtaria MOKADDEM & Mohamed DJEBELLA (Akofena)
Abstract: The current research paper sheds light on the ’problematic of social responsibility’ in an attempt to study the variety of descriptions related to the concept of “responsibility ‘’ through laying out the concept (frames and dimensions), domains (philosophical, legal, social, economic and ethical, etc.) and the practice ; how it is represented in reality. This can be achieved through displaying and analyzing different theories in the field of human and social sciences which have enunciated several principles and ideas drawn mostly from their ideologies.